Using Sartre’s Critique of Dialectical Reason for Managerial Decision-Making - Kleist, Chad (2013)
This article will offer an alternative understanding of managerial decision-making drawing from Sartre’s Critique of Dialectical Reason rather than simply Being and Nothingness. I will begin with a brief explanation of Sartre’s account of freedom in Being and Nothingness. I will then show in the second section how Andrew West uses Sartre’s conception of radical freedom from Being and Nothingness for a managerial decision-making model. In the third section, I will explore a more robust account of freedom from Sartre’s Critique of Dialectical Reason. I will attempt to show that freedom is not simply a matter of choosing (or not choosing) to perform an action, but entails external constraints—including other people. Finally, I will provide the implications of this account of freedom for managerial decision-making. I will show that it’s unreasonable to place full responsibility and/or blame on managers given their constraints. This does not absolve them from responsibility, but better accounts for the way in which we ought to hold them responsible.
Keywords: Critique of dialectical reason; Responsibility; Freedom; Existentialism; moral decision-making; Jean-Paul Sartre